Minimizing the electrosorption of water from humid ionic liquids on electrodes - Bi, Sheng; Wang, Runxi; Liu, Shuai; Yan, Jiawei; Mao, Bingwei; Kornyshev, Alexei A.; Feng, Guang (Nature communications, 2018)
In supercapacitors based on ionic liquid electrolytes, small amounts of absorbed water could potentially reduce the electrochemical window of electrolytes and cause performance degradation. The same would take place if ionic liquids are used as solvents for electrocatalysis involving the dissolved molecular species. In this work, we carry out molecular dynamics simulations, with gold and carbon electrodes in typical ionic liquids, hydrophobic and hydrophilic, to study electrosorption of water. We investigate the effects of hydrophobicity/hydrophilicity of ionic liquids and electrodes on interfacial distribution of ions and electrosorbed water. Results reveal that using hydrophilic ionic liquids would help to keep water molecules away from the negatively charged electrodes, even at large electrode polarizations. This conclusion is supported by electrochemical cyclic voltammetry measurements on gold and carbon electrodes in contact with humid ionic liquids. Thereby, our findings suggest potential mechanisms for protection of electrodes from water electrosorption. Ionic liquid electrolytes can impart increased operational voltage and energy density in supercapacitors, but water may diminish performance. Here the authors show that the hydrophilicity/hydrophobicity of ionic liquids can influence electrosorption of water and ultimately the supercapacitor performance.